The effect of nanoparticles TiO2 on the flexural strength of acrylic resin denture plate - Tandra, Edwin; Wahyuningtyas, Endang; Sugiatno, Erwan (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2018)
Introduction: Acrylic resin is still the most commonly used denture base material due to its ideal properties. However, acrylic resin denture fractures are still considered a major unsolved problem thus the addition of nanoparticles as filler was performed to increase its mechanical properties. The purpose of this study was to discovered the effect of nanoparticles TiO2 on the flexural strength of acrylic resin denture plate. Method: This study used 27 heat-cured acrylic resin specimens sized 65 x 10 x 2.5 mm. The samples were divided into three concentration groups (n = 9), the control group; 1% of nanoparticles TiO2; and 3% of nanoparticles TiO2. The flexural strength was tested using the Universal Testing Machine. All data were analysed using the one-way ANOVA test with 95% confidence level then continued with the Least Significant Difference (LSD) test. Results: There were significant flexural strength differences in different concentration of nanoparticles TiO2. The highest flexural strength value was found in the 1% of nanoparticles TiO2 group (106.99 ± 6.09 MPa), whilst the lowest flexural strength value was found in the 3% of nanoparticles TiO2 group (91.64 ± 5.38 MPa). Significant flexural strength difference was found between the control group and the 1% of nanoparticles TiO2 group, and also between the 1% of nanoparticles TiO2 group with the 3% of nanoparticles TiO2 group (p < 0.05). Conclusion: From this study can be concluded that concentration of 1% of nanoparticles TiO2 was able to increase the flexural strength of acrylic resin denture plate.